2003
DOI: 10.1007/s10157-003-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Interim evidence of the renoprotective effect of the angiotensin II receptor antagonist losartan versus the calcium channel blocker amlodipine in patients with chronic kidney disease and hypertension: a report of the Japanese Losartan Therapy Intended for Global Renal Protection in Hypertensive Patients (JLIGHT) Study

Abstract: Losartan appeared to be efficacious for renoprotection in patients with proteinuric CKD and hypertension, with the mechanism being independent of its antihypertensive action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Forty-seven patients in the losartan group and 40 patients in the amlodi-pine group completed the 12-month study for measurement of urinary protein endpoint. The dietary compliance assessment of 24-h urinary urea nitrogen plus proteins and sodium showed that, there was no significant difference in total protein and NaCl intake between the two drug treatment groups at baseline and no change from baseline to month 3, as reported previously (9). At month 12, again, there was no change from baseline and therefore no difference between the losartan group and the amlodipine group in protein intake or NaCl intake (protein [g/day]: losartan, 50.7 19.7; amlodipine, 53.5 17.0; NaCl [g/day]: losartan, 8.0 3.8; amlodipine, 9.6 3.5).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Forty-seven patients in the losartan group and 40 patients in the amlodi-pine group completed the 12-month study for measurement of urinary protein endpoint. The dietary compliance assessment of 24-h urinary urea nitrogen plus proteins and sodium showed that, there was no significant difference in total protein and NaCl intake between the two drug treatment groups at baseline and no change from baseline to month 3, as reported previously (9). At month 12, again, there was no change from baseline and therefore no difference between the losartan group and the amlodipine group in protein intake or NaCl intake (protein [g/day]: losartan, 50.7 19.7; amlodipine, 53.5 17.0; NaCl [g/day]: losartan, 8.0 3.8; amlodipine, 9.6 3.5).…”
Section: Resultssupporting
confidence: 78%
“…Fifty-seven affiliated clinics in Japan contributed to this study. The overall design of the study has been described previously in an interim report presented at 3 months (9). Males and female outpatients, aged 20-74 years, who had CKD and hypertension and who met the following criteria during the 8-week pretreatment screening period were eligible for the study: 1) CKD: serum creatinine (Scr) levels of 1.5 ≤ Scr 3.0 mg/dl in males of body weight (BW) ≥ 60 kg, and of 1.3 ≤ Scr 3.0 mg/dl in females, or males of BW 60 kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In a larger trial of hypertensive patients, losartan significantly decreased proteinuria more than amlodipine in patients with higher and lower baseline levels of proteinuria. 30 An additional example is a reduction of proteinuria in normotensive patients with focal segmental glomerulosclerosis. 31…”
Section: Losartan and Proteinuriamentioning
confidence: 99%
“…Among these, DHP derivatives and Ca channel blockers have been reported to have strong hypotensive actions and have been indicated for many patients in Japan [ 2 ]. In addition, ARBs have organ-protective effects [ 24 , 25 ], and the low frequency of adverse effects and high tolerability [ 26 ] associated with them are thought to contribute to their widespread use. However, the use of antihypertensive drugs varies across countries [ 5 ].…”
Section: Discussionmentioning
confidence: 99%